The Effect of Fiscal Decentralization on Under-five Mortality in Iran: A Panel Data Analysis - Ali Hussein Samadi; Ali Keshtkaran; Zahra Kavosi; Sajad Vahedi (Kerman University of Medical Sciences, 2013)
BackgroundFiscal Decentralization (FD) in many cases is encouraged as a strong means of improving the efficiency and equity in the provision of public goods, such as healthcare services. This issue has urged the researchers to experimentally examine the relationship between fiscal decentralization indicators and health outcomes. In this study we examine the effect of Fiscal Decentralization in Medical Universities (FDMU) and Fiscal Decentralization in Provincial Revenues (FDPR) on Under-Five Mortality Rate (U5M) in provinces of Iran over the period between 2007 and 2010. MethodsWe employed panel data methods in this article. The results of the Pesaran CD test demonstrated that most of the variables used in the analysis were cross-sectionally dependent. The Hausman test results suggested that fixed-effects were more appropriate to estimate our model. We estimated the fixed-effect model by using Driscoll-Kraay standard errors as a remedy for cross-sectional dependency. ResultsAccording to the findings of this research, fiscal decentralization in the health sector had a negative impact on U5M. On the other hand, fiscal decentralization in provincial revenues had a positive impact on U5M. In addition, U5M had a negative association with the density of physicians, hospital beds, and provincial GDP per capita, but a positive relationship with Gini coefficient and unemployment. ConclusionThe findings of our study indicated that fiscal decentralization should be emphasized in the health sector. The results suggest the need for caution in the implementation of fiscal decentralization in provincial revenues.